Marketing Strategy For Tobacco And Its Industrial Products To Faceglobal Market And Anti-Tobacco Campaign - iryono i (POLITICO, 2019)
During the last decade, tobacco was sharply highlighted by the international community. In global trade, the tobacco business and its industrial products were under pressure from the world through the world health organization that formulates the framework convention on tobacco control (FCTC). The conventions of FCTC aim to control tobacco and its industrial products in the global market, because they can be detrimental to health. This paper aims to review the pattern of tobacco trade in a global market that tends to get discriminated. The method of analysis employed by the author is reviewing the existing journals and conducting observations and discussions related to the problem of tobacco in the global trading. The facts in tobacco trade show that FCTC regulations that have been widely adopted by countries in the world are often tangential to global trade regulations enacted in almost all over the world. Tobacco and its industrial products are subject to discriminatory treatment in global trade. This condition has triggered many parties to trade tobacco illegally, given the need of world tobacco despite pressure always rises about 2% every year along with the increase of world population number. In the business administration review, an objective strategy is needed to address the challenges inherent in the tobacco business. The Paradigm of Resources Based View (RBV) and Market Based View (MBV) in the tobacco business need to be integrated into the internal and external factors of the business, thus the tobacco business can be maintained. A country producing tobacco (for example: Indonesia), must supportits citizen to exist at their business, because they get benefit at tobacco business. The country must safeguard and fight for tobacco to global market without having to experience product discrimination.